Characterization of deep ore-forming fluid in the Zhaoxian gold deposit within the Jiaodong gold province: insights from quartz vein fluid inclusion, in-situ trace element analysis, and S isotopic composition in pyrite - Zhang, Zheming; Zeng, Qingdong; Fan, Hong-Rui; Bai, Rui; Wu, Jinjian; Li, Xinghui; Zhang, Yongwen; Huang, Liangliang (Frontiers in Earth Science, 2024)
The Jiaodong gold province, located in the southeastern margin of the North China Craton, is globally renowned for its substantial gold reserves exceeding 5,000 tonnes. The Zhaoxian gold deposit is part of the significant Jiaojia gold belt within the Jiaodong gold province. Fieldwork has identified four distinct stages of ore formation: an early barren quartz vein stage (Stage 1) containing fine-grained pyrite; a gold-bearing stage (Stage 2) consisting of quartz, pyrite, and native gold; a polymetallic sulfide-rich stage (Stage 3) comprising quartz, polymetallic sulfides, and native gold; and a late-stage (Stage 4) primarily composed of quartz and calcite with minimal pyrite content. Analyses have determined the volatile components, homogenization temperatures, and salinities of fluid inclusions, indicating a medium-temperature, medium-to-low-salinity H₂O-NaCl-CO₂ ± CH₄ fluid system. In Stage 2, the fluctuations in Au and As concentrations, together with oscillating zones and sulfide inclusions, may suggest the process of fluid boiling. Within Stage 3 pyrite, higher concentrations of Ag, Cu, Zn, Cd, In, Pb, and Bi compared to other stages indicate a stable fluid environment. In Stage 4, the elemental composition of pyrite is lower except for Co and Ni, with no observed oscillating zones. δ34S values in the Zhaoxian gold deposit are slightly higher than those in Jiaodong gold district granitoids, but similar to those in gold deposits within the Jiaojia gold belt, suggesting magmatic-hydrothermal ore-forming fluids and fluid-rock interaction during the metallogenic process. In conclusion, the Zhaoxian gold deposit has undergone a complex mineralization process and represents a prototypical magmatic hydrothermal deposit within the Jiaodong region.